Project management the agile way making it work in the enterprise - Goodpasture, John C., 1943- (J. Ross Pub., 2010)
This is a practical guide to Agile methods for project management, and how to apply them effectively. "Project Management the Agile Way" is written specifically for experienced project managers, architects, and systems analysts who have a good understanding of traditional PM techniques, but now need to learn about agile methods for software projects. Featuring reviews of the most popular Agile and iterative methodologies for project management - such as Scrum, XP, Crystal, and EVO - as well as practical tips and advice on how to apply these practices to mainstream projects and how to integrate them with other methodologies used in enterprise, this is a must-have resource for those involved in project management.